Designing Exercise to Improve Bone Health Among Individuals With Cerebral Palsy. Issue 1 (January 2021) - Gannotti, Mary E.; Liquori, Brianna M.; Thorpe, Deborah E.; Fuchs, Robyn K.
Abstract : Purpose: Individuals with cerebral palsy (CP), ambulatory or not, have less bone strength and density than their peers. Aging individuals with CP are at a higher risk for nontraumatic fractures, progressive deformity, pain, and spinal stenosis. Critical periods for skeletal formation are during prepuberty and adolescence. Applying mechanostat theory to exercise design for individuals with CP may be beneficial. Methods: Principles of mechanostat theory, particularly the osteogenic index, is applied to guide the design of exercise programs based on varying levels of physical capacity. Results: Recommendations are made for optimizing dosing of a variety of interventions for improving bone health among individuals with CP based on mechanostat theory with specific type, number of repetitions, and frequency. Conclusions: Researchers and clinicians are called to action to consider the role of exercise throughout the lifespan for all individuals with CP, regardless of level of severity. Abstract : Supplemental Digital Content is Available in the Text.Recommendations are made for optimizing dosing of interventions for improving bone health among individuals with cerebral palsy based on mechanostat theory.